Cryptotanshinone enhances the efficacy of Bcr-Abl tyrosine kinase inhibitors via inhibiting STAT3 and eIF4E signalling pathways in chronic myeloid leukaemia - Rubin Cheng; Yilan Huang; Yun Fang; Qirui Wang; Meixiu Yan; Yuqing Ge (Taylor & Francis Group, 2021)
Context A portion of patients with chronic myeloid leukaemia (CML) develop resistance to the Bcr-Abl tyrosine kinase inhibitors (TKIs), limiting the clinical applications. Previous results have demonstrated the synergistic effects between cryptotanshinone (CPT) and imatinib on apoptosis of CML cells in vitro. Objective To determine the antileukemia effects of CPT and TKIs on the resistant CML cells, and further investigate the effect of combined treatment of CPT and imatinib on tumour growth and apoptosis in the xenograft model and clarify its regulatory mechanisms. Materials and methods The combination effects of CPT and second-generation TKIs were evaluated in resistant CML cells K562-R. CPT and imatinib were orally administered once daily for 21 days on K562-R xenografts in nude mice (6 per group). Tumour proliferation and apoptosis were examined by Ki-67, PCNA and TUNEL staining. The expression levels of apoptotic markers and activities of STAT3 and eIF4E pathways were determined via immunohistochemistry staining and western blotting analysis. Results CPT significantly enhanced the antiproliferative effects of TKIs, via triggering cleavages of caspase proteins, and inhibiting activities of STAT3 and eIF4E pathways. The administration of CPT and imatinib dramatically inhibited the tumour growth of xenografts and achieved a suppression of 60.2%, which is 2.6-fold higher than that of single imatinib group. Furthermore, CPT and imatinib increased the apoptotic rates and markedly decreased the phosphorylation levels of STAT3 and eIF4E. Conclusions Our results demonstrated that CPT could significantly enhance the antileukemia efficacy of TKIs, suggesting the therapeutic potential of CPT to overcome CML resistance.